1997
DOI: 10.1080/15428119791012388
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Exposure to Chemical Agents and Ergonomic Stressors in Tanneries in Kanpur, India

Abstract: In developing countries qualitative assessment of exposure at the workplace may be an essential tool in evaluating hazardous working conditions. This survey reports on qualitative assessment of exposure to chemicals, dust, and ergonomic stressors among 298 workers in 15 tanneries in Kanpur, India. In general, chemical exposure and dermal exposure were highest among beamhouse workers, less for workers involved in dry finishing activities, and lowest for those performing the wet finishing of hides. Dermal exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The mean level of fingernail Cr (1.16 ± 0.02μg/g) was significantly higher in the group of supervisor, plant services, and guards than in the controls, as well as their fingernail Cr levels were higher by 62.1 % (p < 0.05) than those in the controls. Ory et al suggested that nontanning workers, such as packers, and plants services often had chemicals of exposures as they move from one section to the other during their daily work (Ory et al 1997). Based on the above results, we suggest that improvement of the workplace through adequate ventilation should be more practiced in the tannery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean level of fingernail Cr (1.16 ± 0.02μg/g) was significantly higher in the group of supervisor, plant services, and guards than in the controls, as well as their fingernail Cr levels were higher by 62.1 % (p < 0.05) than those in the controls. Ory et al suggested that nontanning workers, such as packers, and plants services often had chemicals of exposures as they move from one section to the other during their daily work (Ory et al 1997). Based on the above results, we suggest that improvement of the workplace through adequate ventilation should be more practiced in the tannery.…”
Section: Discussionmentioning
confidence: 99%
“…The study population consisted of 49 tannery workers. They were classified into three exposure categories based on their operational department, chemical use, and references (Saner et al 1984, Ory et al 1997): 1) 16 pre-tanning and tanning; 2) 18 wet finishing and dry finishing, and 3) 15 supervisor, plant services, and guards. The controls consisted of 33 persons who were not employed in industrial sectors.…”
Section: Study Subjectsmentioning
confidence: 99%
“…There is also significant variation in the scale and types of tanning facilities between developed and developing countries (Stellman, 1998). Tanneries in developed countries like the United States, Australia, and Europe are highly mechanized and use closed automatic systems and many chemicals (Black et al, 2013; Buljan & Kral, 2019), whereas in developing countries like Bangladesh, Pakistan, Afghanistan even India still uses mostly manual work and natural tanning substances with techniques remaining unchanged over a long period (Hashmi et al, 2017; Kesarwani et al, 2015; Öry et al, 1997a).…”
Section: Introductionmentioning
confidence: 99%
“…Workers do not have direct contact with water or chemicals in this stage; however, they may experience exposure to oil products and chemicals while processing wet hides as well as in the dry finishing stage as drying, shaving, buffing, pressing, padding, and spraying (Black et al, 2013; Buljan & Kral, 2019). Exposure to dust particles generated from leather and paint during operating machinery and spraying are the specific hazards in this stage (Öry et al, 1997a). Finally, several workers perform duties as packers, sweepers, carriers, and mixers of chemicals which are considered “miscellaneous.” The workers in this group have the chance for multiple co-exposures as they move from one section to other during their daily work, and their duties may change from time to time.…”
Section: Introductionmentioning
confidence: 99%